Genome-wide identification and expression analyses of the calmodulin and calmodulin-like proteins reveal their involvement in stress response and fruit ripening in papaya - Ding, Xiaochun; Zhang, Linpeng; Hao, Yanwei; Xiao, Shuangling; Wu, Zhengxian; Chen, Weixin; Li, Xueping; Zhu, Xiaoyang (Postharvest biology and technology, 2018)
•41 CaM and CML proteins were identified in the papaya genome.•Bioinformatics analysis showed that they were typical CaM and CML in plant.•Expression analysis showed that CaM and CML were involved in stress responses.•Some CaM/CMLs were rigorously regulated by ethylene (ethephon and 1-MCP).•CaM/CMLs are involved in fruit ripening. Calcium (Ca2+) is an important second messenger involved in diverse developmental and adaptive processes in plants. Calmodulin (CaM) and calmodulin-like (CML) proteins are primary Ca2+ sensors that control diverse cellular functions. In this study, 41 genes encoding CaM and CML proteins were identified in the papaya genome, three of which were CaM and others were CML. Sequence alignment, gene structural and phylogenetic analyses revealed that all CaM/CMLs contained the EF-hand, but not other functional domains, and CaM proteins were quite conservative while CML proteins exhibited sequence diversity and structural multiformity. Promoter analysis identified different types of cis-elements related to plant growth and development, hormone response, light response, stress response and transcriptional enhancement in promoter regions of CpCaM/CML genes. Gene expression analysis showed distinctive expression profiles of the CaM/CMLs in different tissue types, different fruit developmental stages and different fruit storage conditions. Several groups of CaM/CML genes were positively or negatively regulated by high and low temperature stresses, such as CML16, CML17.1, CML24 and CML36, indicating that they may play a role in temperature stress adaption. Notably, some CaM/CML genes were rigorously regulated by ethylene (ethephon and 1-MCP treatment), either in a positive or a negative manner, such as CaM7, CML15, CML16, CML17.1, CML37 and CML46. All these results indicated that CaM and CML gene families might play important roles in fruit development, in response to temperature stresses and in fruit ripening process.